Reformas tributarias y su impacto en el cálculo del impuesto a la renta (ir) para microempresas del sector comercial de la ciudad de Latacunga en el periodo 2019 – 2021. - Cunuhay Umajinga, Franklin Fernando (2023)
The objective of this research project is to analyze the tax reforms and their effect on the calculation of Income Tax in commercial microenterprises caused by the imposition of the Organic Law of Tax Simplification and Progressivity and the Organic Law for Economic Development and Fiscal Sustainability. . It should be noted that in recent years Ecuador has experienced constant tax changes regarding the calculation and settlement of Income Tax, the appearance of new regimes, especially for those entities registered as micro-enterprises.